2006
DOI: 10.1155/2006/218073
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensetive Reaction for the Estimation of Carbaryl Using 4‐4ˊ‐ Diaminodiphenyl Sulfone in Environmental Samples

Abstract: A rapid, sensitive Spectrophotometric method for the determination of ultra trace amount of carbaryl (1- Napthyl-N- Methyl Carbamate) is proposed. The method is based on an alkali hydrolysis of carbaryl in the presence of methanolic KOH, followed by coupling with diazotized 4-41- diaminodiphenyl sulfone in an alkaline medium. The water soluble pink dye obtained shows an absorption maximum at 540 nm. The system obeys Beer’s law over the range of 0.06-2.0μg mL-1. The absorptivity of the coloured product is 7.014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The acute oral LD 50 for rats is 850 mg/kg [4]. It has been reported that carbaryl causes alteration of liver microsomal enzymes, neurotoxicity, immunotoxic effects, histopathological changes in the testis, haemoatopoietic alterations [5][6][7][8][9]. The extensive use of this insecticide poses a serious risk to both the environment and the human health due to direct exposure or through residues in the food and drinking water [10].…”
mentioning
confidence: 99%
“…The acute oral LD 50 for rats is 850 mg/kg [4]. It has been reported that carbaryl causes alteration of liver microsomal enzymes, neurotoxicity, immunotoxic effects, histopathological changes in the testis, haemoatopoietic alterations [5][6][7][8][9]. The extensive use of this insecticide poses a serious risk to both the environment and the human health due to direct exposure or through residues in the food and drinking water [10].…”
mentioning
confidence: 99%